2013
DOI: 10.1002/jms.3218
|View full text |Cite
|
Sign up to set email alerts
|

Sodium adduct formation efficiency in ESI source

Abstract: Formation of sodium adducts in electrospray (ESI) has been known for long time, but has not been used extensively in practice, and several important aspects of Na(+) adduct formation in ESI source have been almost unexplored: the ionization efficiency of different molecules via Na(+) adduct formation, its dependence on molecular structure and Na(+) ion concentration in solution, fragmentation behaviour of the adducts as well as the ruggedness (a prerequisite for wider practical use) of ionization via Na(+) add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 27 publications
7
114
0
1
Order By: Relevance
“…The mechanisms of ESI are complex and numerous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been carried out for its elucidation. It has been shown that the electrospray ionization efficiency (IE) [16] of an analyte is influenced by its molecular structure as well as the solvent (including its pH and additives) and the MS system.…”
Section: E Lectrospray Ionization Mass-spectrometry (Esi/ms) Is Amentioning
confidence: 99%
See 4 more Smart Citations
“…The mechanisms of ESI are complex and numerous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been carried out for its elucidation. It has been shown that the electrospray ionization efficiency (IE) [16] of an analyte is influenced by its molecular structure as well as the solvent (including its pH and additives) and the MS system.…”
Section: E Lectrospray Ionization Mass-spectrometry (Esi/ms) Is Amentioning
confidence: 99%
“…For a better understanding of the ESI process, IE scales, in both positive [7,9] and negative [8] mode, established for fixed solvent compositions are useful. In both modes, IE prediction models have been obtained [3,7,8,20].…”
Section: E Lectrospray Ionization Mass-spectrometry (Esi/ms) Is Amentioning
confidence: 99%
See 3 more Smart Citations